Analisis Perbandingan Sistem Kinerja Motor Penggerak Pada Mobil Listrik Kapasitas 75 kWh - Indriawan Viantama; Budhi Muliawan Suyitno (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2021)
Population growth and the increasingly rapid industrial technology to 4.0. So that there was an electric car with an electric motor as the driving force. At first, electric cars used a DC motor system. But the triumph of this DC motor is not long in coming because problems arise when compared to induction motors such as complicated maintenance, much higher prices, and heavier weight than induction motors. In an induction motor, the control is believed to be easier than a DC motor. The induction motor is believed to make it possible to drive an electric car. The advantage of using this induction motor is that it has durability, reliability, if exposed to interference, it remains strong, easy to maintain, and the ability to operate in extreme environments. These advantages can replace the use of DC motors. Where the induction motor receives power from a rechargeable battery, so that the analysis of data from an induction motor for an electric car with the calculation of the electric motor rotation is 1,500 rpm, the motor power itself is 375 kW, the maximum and minimum torque generated is 582 Nm and 271 , 2 Nm, with a battery life of 189.3 hours. The resulting acceleration to reach speeds of 0-100 km / h only takes 5 seconds.